INFLUENCE OF SCHOOL POLICY AND GUIDELINES ON PROMOTION OF CHILD-FRIENDLY SCHOOLS MODEL IN PUBLIC PRIMARY SCHOOLS IN MERU COUNTY, KENYA - Munene, Gichobi, Peter; Severina , Dr. Mwirichia,; Lucy, Dr. Ikiara, (IJRDO- Journal of Educational Research, 2022)
Good governance practices in learning institutions are important for effective management, positive learning experiences, improved school systems and quality of learning outcomes. The objective of the study was to establish the influence of school policy and guidelines on promotion of child-friendly schools’ model in public primary schools in Meru county, Kenya. The study was founded on transformational leadership theory by Burns (1978), and social systems theory (Katz & Kahn,1978). A correlational design in a mixed methods approach was adopted, integrating both quantitative and qualitative methods. Target population was 6,814 individuals, comprising of 647 headteachers, 647 chairpersons of boards of management, and 5,520 teachers in public primary schools in Meru county. Slovin’s formula was used to select a sample of 378 individuals. Self-designed questionnaires with closed ended items were used to collect quantitative data from teachers and headteachers. Qualitative data was obtained from chairpersons of boards of management through interview guide. Descriptive statistics were used for quantitative data analyses. Qualitative data was analyzed in thematic content analysis. Inferential statistics were conducted through correlation analysis using Pearson’s product moment correlation coefficient for the purpose of testing the hypothesis. The findings revealed that school policy and guidelines significantly and positively influenced promotion of CFS model (r (286) = 0.16, P< 0.05). The study therefore recommended that teachers needed more specific training on learners’ gender dynamics and unique learning needs of both boys and girls with the aim of achieving truly gender responsive and supportive learning environments. Further, the Ministry of Education through the Kenya Institute of Curriculum Development ought to develop a specific training module focusing on the components of CFS, with the aim of enhancing teacher specific skills towards holistically promoting quality education. Good governance practices in learning institutions are important for effective management, positive learning experiences, improved school systems and quality of learning outcomes. The objective of the study was to establish the influence of school policy and guidelines on promotion of child-friendly schools’ model in public primary schools in Meru county, Kenya. The study was founded on transformational leadership theory by Burns (1978), and social systems theory (Katz & Kahn,1978). A correlational design in a mixed methods approach was adopted, integrating both quantitative and qualitative methods. Target population was 6,814 individuals, comprising of 647 headteachers, 647 chairpersons of boards of management, and 5,520 teachers in public primary schools in Meru county. Slovin’s formula was used to select a sample of 378 individuals. Self-designed questionnaires with closed ended items were used to collect quantitative data from teachers and headteachers. Qualitative data was obtained from chairpersons of boards of management through interview guide. Descriptive statistics were used for quantitative data analyses. Qualitative data was analyzed in thematic content analysis. Inferential statistics were conducted through correlation analysis using Pearson’s product moment correlation coefficient for the purpose of testing the hypothesis. The findings revealed that school policy and guidelines significantly and positively influenced promotion of CFS model (r (286) = 0.16, P< 0.05). The study therefore recommended that teachers needed more specific training on learners’ gender dynamics and unique learning needs of both boys and girls with the aim of achieving truly gender responsive and supportive learning environments. Further, the Ministry of Education through the Kenya Institute of Curriculum Development ought to develop a specific training module focusing on the components of CFS, with the aim of enhancing teacher specific skills towards holistically promoting quality education.